25 UMPSA lecturers listed among the world’s top 2% scientists - Mimi Rabita, Abd Wahit (UMPSA, 2025)
PEKAN, 8 October 2025 - A total of 25 lecturers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were listed among the world’s top 2% scientists under the Single Year Achievement category, with 15 of them also listed under the Career-Long Achievement category.